Genealogía del Gravamen a los Movimientos Financieros : el colofón del acto bienvenidos al futuro y el prolegomeno del acto ascenso financiero : el guión de una obra inconclusa que prometió ser (2017)
The document is a historical look at the process that led to the introduction of the Bank Debit Taxes (BDT). In this case, the economic component is complemented by the relationships that are developed between the different agents, and how from these confrontations the BDT ends up being one of the means to understand how the financial system becomes the center of the Colombian economy.